El pensamiento espacial en el aprendizaje de simetría y teselados a través del arte en la educación básica - Rojas Rodríguez, Yerson Eulises (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: The research objective was to analyze the development of spatial thinking processes through the learning of basic notions of tessellations and symmetry. By means of the implementation of a didactic proposal centered on art, with analogical and technological mediation, to elementary school students participating in a mathematics club. Initially, a process of exploration of the level of knowledge possessed by basic education students was carried out, through an initial diagnosis, about the basic notions of tessellations and symmetry in Euclidean geometry. This allowed the design and application of some didactic sequences to enhance the construction of spatial thinking through the articulation of geometry and art. In the development of the research process, the analysis and construction of meaning of teaching practices regarding the didactic strategies that support the teaching and learning process of mathematics with the participation of different actors, seeking to motivate the student in the development of reasoning, resolution and communication competencies in spatial thinking were proposed. Finally, this project was based on a qualitative research under the action participation model.